2020
DOI: 10.1097/spv.0000000000000838
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Urodynamic Parameters in Women With Overactive Bladder Symptoms

Abstract: Objectives This study aimed to identify differences in severity of overactive bladder (OAB) symptoms in women of different races and ethnicities using urodynamic study (UDS) parameters. Methods We performed a 5-year retrospective chart review from January 2014 to January 2019 of women 18 years and older who endorsed OAB symptoms and underwent UDS at a racially and ethnically diverse academic urban medical center. Logistic and linear regressions were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Additionally, compared with White women, Black women were 3.4‐fold more likely to have detrusor overactivity (95% confidence interval [CI]: 0.99–11.40) and had lower volumes at time of “strong desire” (−102.6 ml, p = 0.003) on urodynamic testing. Similarly, Hispanic women had on average 75.88 ml less volume at sensation of “strong desire” ( p = 0.016) than did White women 18 . Although the physiologic mechanism remains unclear, this study suggests that race and epigenetic influences contribute to the experience of OAB pathology, and that race is a proxy for an unmeasured determinant of OAB severity.…”
Section: Overactive Bladder Prevalence In Marginalized Populationsmentioning
confidence: 69%
See 2 more Smart Citations
“…Additionally, compared with White women, Black women were 3.4‐fold more likely to have detrusor overactivity (95% confidence interval [CI]: 0.99–11.40) and had lower volumes at time of “strong desire” (−102.6 ml, p = 0.003) on urodynamic testing. Similarly, Hispanic women had on average 75.88 ml less volume at sensation of “strong desire” ( p = 0.016) than did White women 18 . Although the physiologic mechanism remains unclear, this study suggests that race and epigenetic influences contribute to the experience of OAB pathology, and that race is a proxy for an unmeasured determinant of OAB severity.…”
Section: Overactive Bladder Prevalence In Marginalized Populationsmentioning
confidence: 69%
“…Similarly, Hispanic women had on average 75.88 ml less volume at sensation of "strong desire" (p = 0.016) than did White women. 18 Although the physiologic mechanism remains unclear, this study suggests that race and epigenetic influences contribute to the experience of OAB pathology, and that race is a proxy for an unmeasured determinant of OAB severity.…”
Section: Overactive Bladder Prevalence In Marginalized Populationsmentioning
confidence: 78%
See 1 more Smart Citation
“…Questionnaire studies have found that race/ethnicity is associated with OAB symptoms, with African American and Hispanic women 3-4 times more likely to have OAB than White or Asian women [11,12]. In a more recent study examining differences in urodynamic parameters in women with OAB, African American women were more likely to endorse OAB symptoms and have detrusor overactivity on urodynamics than Hispanic women, and Hispanic women were more likely to report mixed urinary incontinence (MUI) than African American women [13]. However, the authors admit the limitations of this study include its small sample size, retrospective nature and inclusion of patients at a single institution.…”
Section: Prevalencementioning
confidence: 99%
“…A few research groups have studied racial and ethnic differences in the prevalence of urological disorders. Zuo et al [16] conducted a study to identify differences in severity of overactive bladder (OAB) in women of different races, and Van Den Eeden et al [17] sought to examine if there are racial or ethnic differences in lower urinary tract symptoms (LUTS) in men. A recent study showed more than 70% of urinary incontinence is associated with bother regardless of race or ethnicity [18].…”
Section: Introductionmentioning
confidence: 99%